Reactivity of bromoselenophenes in palladium-catalyzed direct arylations - Aymen Skhiri; Ridha Ben Salem; Jean-François Soulé; Henri Doucet (Beilstein Journal of Organic Chemistry, 2017)
The reactivity of 2-bromo- and 2,5-dibromoselenophenes in Pd-catalyzed direct heteroarylation was investigated. From 2-bromoselenophene, only the most reactive heteroarenes could be employed to prepare 2-heteroarylated selenophenes; whereas, 2,5-dibromoselenophene generally gave 2,5-di(heteroarylated) selenophenes in high yields using both thiazole and thiophene derivatives. Moreover, sequential catalytic C2 heteroarylation, bromination, catalytic C5 arylation reactions allowed the synthesis of unsymmetrical 2,5-di(hetero)arylated selenophene derivatives in three steps from selenophene.